Roles and Contributions of Private Tertiary Education in Malaysia - Cheng, Sheila; Chiang, Jeffrey C.L (2019)
It has been 62 years of nation building for Malaysia since 1957, and the tertiary education sector has been transformed tremendously. The legislative changes made in 1996 has changed the exclusiveness of public higher education delivery to their coexistence with the private higher education institutions. The higher education sector has been mushrooming into hundreds of public and private universities and colleges, operating together with approval of the Government. Over the last 40 years, this system has enabled a significant increase of Malaysians school graduates to have accessed to the tertiary education. The enrolment rates are approximately 44 per cent in comparison to 14 per cent in the 1970s and 1980s. Almost 1.3 million Malaysian youths are pursuing tertiary education now, of which 500,000 are enrolled in the 20 public universities and more than 600,000 are registered in PIHLs. The objective of this paper is to review and investigate the roles and contributions of private tertiary education to nation building in Malaysia, in the aspect of the human capital and economic development. This study adopts a qualitative approach with a focus on multiple cases of private institutes of higher learning (PIHL). The selected cases share a common characteristics in their alignment and compliance to the requirements as approved educational institutions in the country, and their pursuance to be sustainable and relevant to all stakeholders. The findings also show that PIHLs have contributed substantially to the nation's education sector, such as prudent spending in quality facility, offering specialized courses, reduce burden of the Government and collaborate well with reputable international universities. Further to that, graduates from the PIHLs are able to bridge the gap of the increasing global demand for higher education, and the needs for a highly skilled workforce for the knowledge economy.